Clinical InvestigationsHDR and LDR Brachytherapy in the Treatment of Lip Cancer: the Experience of the Catalan Institute of Oncology - Ayerra, Arrate Querejeta; Mena, Estefanía Palacios; Fabregas, Joan Pera; Miguelez, Cristina Gutiérrez; Guedea, Ferran (Journal of Contemporary Brachytherapy, 2010)
Purpose: Lip cancer can be treated by surgery, external radiotherapy, and/or brachytherapy (BT). In recent years, BT has become increasingly favored for this type of cancer. The aim of the present study was to analyze local control and survival of patients treated at our institution between July 1989 and June 2008. Material and methods: We performed a retrospective study of 121 patients (109 males and 12 females) who underwent lip cancer brachytherapy from July 1989 to June 2008. Median age was 67 years and median follow-up was 31.8 months (range 20-188 months). Out of 121 patients, 100 (82.6%) were treated with low dose rate (LDR) BT while the remaining 21 patients (17.4%) received high dose rate (HDR) BT. Results: The most common cell type was squamous cell carcinoma (115 cases; 95%) and most tumors were located on the lower lip (107 patients; 88.4%). Most cases were either stage T1 (62 patients; 51.2%), or T2 (44 cases; 36.4%). After 15 years of follow-up, overall survival was 89.5%, cause-specific survival 97.8%, and disease-free survival 86.6%. Local, regional, and distant control at 15 years were 90%, 92%, and 98.8%, respectively. Grade 3 mucosal toxicity was observed in 23% of patients treated with LDR compared to 33% of HDR patients, and grade 4 mucosal toxicity in 9% versus 0% in the HDR group. Conclusions: Our findings confirm that brachytherapy is an effective treatment for lip cancer. The results from our series are in line with those published elsewhere. Based on our limited data, HDR appears to be equally as good as LDR, although this needs to be confirmed by further studies.